Carbon dioxide flow and interactions in a high rank coal: Permeability evolution and reversibility of reactive processes. (March 2018) - Hadi Mosleh, Mojgan; Turner, Matthew; Sedighi, Majid; Vardon, Philip J.
Abstract: Uncertainties exist on the efficiency of CO2 injection and storage in deep unminable coal seems due to potential reduction in the permeability of coal that is induced by CO2 adsorption into the coal matrix. In addition, there is a limited knowledge about the stability of CO2 stored in coal due to changes in gas partial pressure caused by potential leakage. This paper presents an experimental study on permeability evolution in a high rank coal from South Wales coalfield due to interaction with different types of gases. The reversibility of the processes and stability of the stored CO2 in coal are investigated via a series of core flooding experiments in a bespoke triaxial flooding setup. A comprehensive and new set of high-resolution data on the permeability evolution of anthracite coal is presented. The results show a considerable reduction of permeability above 1.5 MPa CO2 pressure that is correlated with the coal matrix swelling induced by CO2 adsorption. Notably studied in this work, the chemically-induced strain due to gas sorption into coal, that has been isolated and quantified from the mechanically-induced strain as a result of changes in effective stress conditions. The results of post-CO2 core flooding tests using helium (He), nitrogen (N2 ) and methane (CH4 ) demonstrated a degree of restoration of the initial permeability. The injection of N2 showed no significant changes in the coal permeability and reversibility of matrix swelling. The initial permeability of the coal sample was partially restored after replacing N2 by CH4 . Observation of permeability evolution indicates that the stored CO2 has remained stable in coal under the conditions of the experiments.